Polityka językowa w zakresie nauczania pierwszego języka obcego w wielojęzycznym kraju na przykładzie Szwajcarii – inspirujące doświadczenie - Stępkowska, Agnieszka (Neofilolog, 2019)
The article analyses the Swiss language policy, language planning and the partner – language model offered by the Swiss educational system. The Swiss language policy is most focused on extra-linguistic aims dealing with the changes in the social distribution of languages, and the promotion of multilingualism. Switzerland oscillates between two systems: the traditional language – partner model, and the choice of a language of wider communication (English). Much is indicative of the fact that now Swit-zerland is getting ready for multilingual future with English at hand.